Intervention for Sleep and Pain in Youth (ISPY-RCT): protocol for a two-phase randomized controlled trial of sequenced cognitive-behavioral therapy for insomnia and pain management in adolescents with migraine - Emily F. Law; Lee Ritterband; Chuan Zhou; Tonya M. Palermo (Trials, 2023)
Abstract Background Migraine is a major pediatric health problem impacting 10–12% of youth. About 1 in 3 youth with migraine are diagnosed with insomnia. Sleep and migraine share a cyclical relationship, and data indicate that insomnia symptoms increase migraine severity. CBT for insomnia (CBT-I) has demonstrated efficacy for improving insomnia in adults with migraine and other pain conditions; however, effects in youth have not been evaluated. Moreover, in adults, there is some indication that CBT-I may lead to changes in pain after there are sustained improvements in sleep, but this has never been empirically tested. Cognitive-behavioral therapy for pain management (CBT-Pain) is an established treatment approach for youth with migraine, leading to reductions in headache frequency and disability. In the proposed study, we will address these gaps in knowledge by using an innovative two-phase trial design to (1) test the efficacy of Internet-delivered CBT-I intervention for youth with migraine and comorbid insomnia compared to Internet-delivered sleep education for modifying sleep and (2) investigate how changes in sleep may modify the response to Internet-delivered CBT-Pain intervention. Methods We will study a cohort of 180 adolescents, ages 11–17 years, with migraine (with or without aura, chronic migraine) and comorbid insomnia. In phase 1, youth will be randomly assigned to receive Internet-delivered CBT-I intervention or Internet sleep education control. In phase 2, all youth will receive Internet-delivered CBT-Pain intervention. Assessments will occur at baseline, immediately after phase 1 intervention, immediately after phase 2 intervention, and 6 months post-intervention. We will use a comprehensive multidimensional assessment of sleep and headache including self-report questionnaires, ambulatory actigraphy monitoring, and 14-day daily diaries. Discussion Given the high prevalence of insomnia in adolescents with migraine, an extension of CBT-I intervention to this population will address an important gap in clinical practice and in conceptual understanding of the relationship between sleep and migraine. By testing a separate CBT-I intervention, we will be able to apply this treatment in the future to other pediatric populations (e.g., cancer, arthritis) who commonly experience comorbid insomnia. Trial registration ClinicalTrials.gov NCT04936321. Registered on June 23, 2021.